CLEAR - Effect of contact lens materials and designs on the anatomy and physiology of the eye. Issue 2 (April 2021) - Morgan, Philip B.; Murphy, Paul J.; Gifford, Kate L.; Gifford, Paul; Golebiowski, Blanka; Johnson, Leah; Makrynioti, Dimitra; Moezzi, Amir M.; Moody, Kurt; Navascues-Cornago, Maria; Schweizer, Helmer; Swiderska, Kasandra; et al.
Abstract: This paper outlines changes to the ocular surface caused by contact lenses and their degree of clinical significance. Substantial research and development to improve oxygen permeability of rigid and soft contact lenses has meant that in many countries the issues caused by hypoxia to the ocular surface have largely been negated. The ability of contact lenses to change the axial growth characteristics of the globe is being utilised to help reduce the myopia pandemic and several studies and meta-analyses have shown that wearing orthokeratology lenses or soft multifocal contact lenses can reduce axial length growth (and hence myopia). However, effects on blinking, ptosis, the function of Meibomian glands, fluorescein and lissamine green staining of the conjunctiva and cornea, production of lid-parallel conjunctival folds and lid wiper epitheliopathy have received less research attention. Contact lens wear produces a subclinical inflammatory response manifested by increases in the number of dendritiform cells in the conjunctiva, cornea and limbus. Papillary conjunctivitis is also a complication of all types of contact lenses. Changes to wear schedule (daily disposable from overnight wear) or lens materials (hydrogel from SiHy) can reduce papillary conjunctivitis, but the effect of such changes on dendritic cell migration needs further study. These changes may be associated with decreased comfort but confirmatory studies are needed. Contact lenses can affect the sensitivity of the ocular surface to mechanical stimulation, but whether these changes affect comfort requires further investigation. In conclusion, there have been changes to lens materials, design and wear schedules over the past 20+ years that have improved their safety and seen the development of lenses that can reduce the myopia development. However, several changes to the ocular surface still occur and warrant further research effort in order to optimise the lens wearing experience.